A case study of helium recovery from Australian natural gas. (May 2022) - McElroy, Luke; Xiao, Gongkui; Weh, Roman; May, Eric F.
Abstract: Helium occurs in commercial quantities in some natural gas fields and global production is dominated by the few countries that recover helium as a byproduct of natural gas. In this study, project expense and production capacity data were gathered for nine helium plants across six countries, giving a current dataset for early screening of new helium projects. Because natural gas companies often do not recognise the value of the helium contained in their feedstocks, a profitability analysis was then performed on a plant producing 913 tonnes of liquid helium per year. Base case results show a discounted payback period of 2.4 years and 39.9% discounted cash flow rate of return, clearing typical investment thresholds. Finally, Australia's helium resources and natural gas infrastructure were analysed for helium recovery opportunities not covered by other published surveys, with a pipeline compressor station in the Northern Territory identified as being equipped to generate a helium feedstock from the helium-rich Amadeus basin. Considered together, this study provides economic data relevant to industry worldwide, and explores specific options for Australia, as a natural gas producer and exporter, to increase its helium production capacity and thereby improve global helium supply security. Graphical abstract: Image 1 Highlights: New helium plant dataset that supports cost estimation of future projects. Profitability study of helium recovery from natural gas; investment criteria met. Pipeline compressor station in Northern Territory found to suit helium recovery.